Association between thyroid disorders and abnormal uterine bleeding in reproductive ages - Shawl, Aiyleen S.; Naz, Massarat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abnormal uterine bleeding (AUB) means any bleeding that is not normal in amount, duration, frequency, and cyclicity. It is a common disorder occurring in reproductive age group females. It can be understood as bleeding that occurs from the uterus outside the normal parameters and there are no structural defects in the genital tract. One of the most common associations with AUB is thyroid dysfunctions. Hence, this study aimed to see the incidence of thyroid-related disorders in AUB and also to assess the menstrual pattern. Methods: A total 100 women suffering from AUB who presented to OPD of the gynecology department of L D Hospital Srinagar, Jammu and Kashmir were recruited in the study. All females in 19 to 45 years of age group with abnormal uterine bleeding were included excluding those with a previously known thyroid disorder, abortion history within 3 months, etc. Thyroid function tests were done in all along with ultrasonography of the pelvis region. Data were analyzed using SPSS software v.23.0. and Microsoft office 2007. Results: The bleeding abnormality that was found in most of the women was heavy menstrual bleeding. Out of the 100 patients taken into study 11 had thyroid disorders, out of which subclinical hypothyroidism was most prevalent accounting for 8 cases, 2 cases were found to have hypothyroidism and 1 case of hyperthyroidism was detected. Conclusions: Abnormal uterine bleeding has a strong association with thyroid disorders. The most common type of disorder is subclinical hypothyroidism. Thus, all patient of AUB must be evaluated for thyroid dysfunction.